Toxicity and safety study of silver and gold nanoparticles functionalized with cysteine and glutathione - Pem, Barbara; Pongrac, Igor M.; Ulm, Lea; Pavičić, Ivan; Vrček, Valerije; Domazet Jurašin, Darija; Ljubojević, Marija; Krivohlavek, Adela; Vinković Vrček, Ivana (Beilstein Journal of Nanotechnology, 2019)
This study was designed to evaluate the nano–bio interactions between endogenous biothiols (cysteine and glutathione) with biomedically relevant, metallic nanoparticles (silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs)), in order to assess the biocompatibility and fate of nanoparticles in biological systems. A systematic and comprehensive analysis revealed that the preparation of AgNPs and AuNPs in the presence of biothiols leads to nanoparticles stabilized with oxidized forms of biothiols. Their safety was tested by evaluation of cell viability, reactive oxygen species (ROS) production, apoptosis induction and DNA damage in murine fibroblast cells (L929), while ecotoxicity was tested using the aquatic model organism Daphnia magna. The toxicity of these nanoparticles was considerably lower compared to their ionic metal forms (i.e., Ag+ and Au3+). The comparison with data published on polymer-coated nanoparticles evidenced that surface modification with biothiols made them safer for the biological environment. In vitro evaluation on human cells demonstrated that the toxicity of AgNPs and AuNPs prepared in the presence of cysteine was similar to the polymer-based nanoparticles with the same core material, while the use of glutathione for nanoparticle stabilization was considerably less toxic. These results represent a significant contribution to understanding the role of biothiols on the fate and behavior of metal-based nanomaterials.
Keywords: biocompatibility; cysteine; ecotoxicity; glutathione; nano–bio interactions; nanosafety; nanotoxicity